THE POTENTIAL STUDY OF BIFLAVONOID COMPOUNDSFROM THE LEAVES OF AGATHIS DAMMARA (ARAUCARIACEAE) AS ANTIALZHEIMER BY IN SILICO - Rosalba Irsal, Katrina
Alzheimer's disease is a degenerative brain disorder that is the most common cause of dementia. This disease is characterized by a decline in cognitive abilities. One of the factors that contributes to Alzheimer's disease is the accumulation of -amyloid (amyloid plaques) on the amyloid precursor protein (APP) by BACE-1. The current available treatments for Alzheimer's disease do not specifically target amyloid plaques and often come with side effects. Aduhelm, a monoclonal antibody that targets amyloid plaques, is available, but its price is extremely expensive dan controversial among doctors and researchers. Recent research has found a relationship between flavonoid intake and Alzheimer's disease. One of the plants in Indonesia known to contain flavonoids is the Agathis genus, which belongs to the Araucariaceae family. One species of Agathis that is A. dammara, commonly known as "damar." The isolation of secondary metabolites from the leaves of Agathis dammara species in Indonesia, growing in the Cikole region, has revealed the presence of several biflavonoid compounds. Apart from Cikole, A. dammara is widely found in Bandung city, as it is utilized for its role in becoming the city's lungs. However, phytochemical study, has not been conducted yet. Therefore, this research aims to isolate and characterize the structure of secondary metabolites from A. dammara plants that grow in Bandung city, as well as study the potential bioactivity of biflavonoids from A. dammara leaves as BACE-1 inhibitors through in silico analysis. The isolation of biflavonoids from A. dammara was carried out through several stages, starting with the maceration of leaves powder with acetone, followed by the separation of chlorophyll from the extract. The chlorophyll-free fraction was subjected to separation and purification using Vacuum Liquid Chromatography (VLC) and Gravity Column Chromatography (GCC) methods. The isolated biflavonoids were subsequently elucidated, and their structures are identified using ID and 2D NMR spectroscopy. The isolation of compounds from the leaves of A. dammara plants originating from Bandung city has been conducted, resulting in three compounds. One of the compounds is a new compound, i.e., 4',7",4"'-tri-0- methylcupressuflavone, while two other compounds were 7,4',7",4"'-tetra-0- methylcupressuflavone, and 7,4',7''-tri-0-methylcupressuflavone that have also been isolated from A. dammara leaves in Cikole. To discover their potential as an antialzheimers agent, particularly as a BACE-1 inhibitor, through in silico studies, the compounds were subjected to molecular docking analysis. In this analysis, the interactions between the isolated compounds and the target protein of BACE-1 were compared to quercetin. The software used for the analysis was Autodock Vina, and the results were visualized using Biovia. The 4',7'',4"'-tri-0-methylcupressuflavone compound exhibited a docking score of -8.5 kcal/mo!. The results of the entire in silico analysis indicated that the biflavonoid with the highest potential as a BACE-1 inhibitor is bilobetin, with a docking score of -11.1 kcal/mo!. The results of the interaction analysis revealed that bilobetin can inhibit BACE-1 by forming interactions with important residues, one of them were the catalytic site residues Asp32 and Gly230 on the active site of BACE-1.